2002
DOI: 10.1071/py02042
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Patient Enablement: The Role of Doctors' Helpgiving Style, Patient and Visit Characteristics

Abstract: Patient enablement is a possible outcome of primary health care consultations and has been employed as a marker of effective helpgiving. We studied predictors of patient enablement, investigating the relative contribution of patient characteristics (gender, age, occupational status, and perceived health status), visit characteristics (length of consultation, duration of physician-patient relationship, and frequency of consultations), and the physician's reported helpgiving style (level of encouragement of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…However, there is already some published evidence to support the benefits of consultations offering a more patient‐centred approach 7. Where patients ‘know the doctor well’, as in this study, consultations over 15 minutes have been shown to be helpful for the patients in enablement and promoting better self‐efficacy skills 8. An existing positive therapeutic relationship between HCP and patient, and time seem to be key.…”
Section: Discussionmentioning
confidence: 55%
“…However, there is already some published evidence to support the benefits of consultations offering a more patient‐centred approach 7. Where patients ‘know the doctor well’, as in this study, consultations over 15 minutes have been shown to be helpful for the patients in enablement and promoting better self‐efficacy skills 8. An existing positive therapeutic relationship between HCP and patient, and time seem to be key.…”
Section: Discussionmentioning
confidence: 55%
“…Our study is the first to highlight the importance of twoway trust, distinguishing it from studies that report the importance of patient's trust in GPs and GPNs (Alazri & Neal 2003, Hudon et al 2011a, Banerjee & Sanyal 2012. Two-way trust transforms consultations into 'meetings between experts' (Tuckett et al 1985), smoothing the way for participatory style consultations and shared decision-making (Freeman et al 2002, Simmons & Winefield 2002, Wensing et al 2007, Ruiz-Moral 2010. Health providers who listen are valued by patients (Rohrer et al 2008, Halcomb et al 2013, further evidenced by patients in this study, who felt valued by nurses who listened and acknowledged their expertise (Hudon et al 2013).…”
Section: Discussionmentioning
confidence: 90%
“…), smoothing the way for participatory style consultations and shared decision‐making (Freeman et al . , Simmons & Winefield , Wensing et al . , Ruiz‐Moral ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the PEI as originally designed [4]: six questions with four possible responses scored as zero (“same or less”, or “Not Applicable”), one (better/more) or two (much more/better), with a per-patient PEI score being the sum of scored responses. This results in a scale from zero to twelve, with an expected linear distribution (as opposed to satisfaction measures, which are typically positively skewed by patient reluctance to express dissatisfaction with individual clinicians [5,13,20]).…”
Section: Methodsmentioning
confidence: 99%